Global and regional spillovers in emerging stock markets : a multivariate GARCH-in-mean analysis - John Beirne; Guglielmo Maria Caporale; Marianne Schulze-Ghattas; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper examines global (mature market) and regional (emerging market) spillovers in local emerging stock markets. Tri-variate VAR GARCH(1,1)-in-mean models are estimated for 41 emerging market economies (EMEs) in Asia, Europe, Latin America, and the Middle East. The models capture a range of possible transmission channels: spillovers in mean returns, volatility, and cross-market GARCH-in-mean effects. Hypotheses about the importance of different channels are tested. The results suggest that spillovers from regional and global markets are present in the vast majority of EMEs. However, the nature of crossmarket linkages varies across countries and regions. While spillovers in mean returns dominate in emerging Asia and Latin America, spillovers in variance appear to play a key role in emerging Europe. There is also some evidence of cross-market GARCH-in-mean effects. The relative importance of regional and global spillovers varies too, with global spillovers dominating in Asia, and regional spillovers in Latin America and the Middle East.
Keywords: F30; G15; 330; volatility spillovers; contagion; stock markets; emerging markets; Börsenkurs; Volatilität; Aktienmarkt; Internationaler Preiszusammenhang; Ansteckungseffekt; Internationaler Finanzmarkt; Aufstrebende Märkte; Welt; Schwellenländer